Chapter Spatial displacement of nearshore vegetation in response to artificial changes in coastal morphology - Cutajar, Martina (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
This study characterizes the zonation of coastal vegetation in six coastal sites in Malta. The vegetation sequence on the coastal zone is predictable and displaces in response to changes in shoreline. The halophyte Limbarda crithmoides was used as an indicator species to 'locate' the position of the sequence. The vegetation surveys were used to construct a Gaussian distribution model for this species. Peak density and peak distance from the shore were positively correlated with exposure. The models were used to simulate the predicted shift of the vegetation in response to a modified shoreline